Risk of posterior capsular rupture during phacoemulsification cataract surgery in eyes with previous intravitreal antivascular endothelial growth factor injections. Issue 2 (February 2020) - Nagar, Anindyt M.; Luis, Joshua; Kainth, Nimrath; Panos, Georgios D.; Mckechnie, Cordelia J.; Patra, Sudeshna
Abstract : Previous intravitreal anti-VEGF injections are a significant under reported risk factor for posterior capsular rupture during cataract surgery. There is a dose-related risk, which is statistically and clinically significant. Abstract : Purpose: To investigate whether previous intravitreal antivascular endothelial growth factor (VEGF) injections are a predictor for posterior capsular rupture (PCR) during phacoemulsification cataract surgery. Setting: Whipps Cross University Hospital Eye Treatment Centre, London, United Kingdom. Design: Single-center, retrospective, electronic medical record (EMR) database study with univariate analysis. Methods: Data were extracted from an EMR system on eyes undergoing phacoemulsification surgery between August 1, 2016, and January 1, 2018. Patient demographics, indication for intravitreal therapy, treatment type, the number of previous intravitreal injections (IVIs), diabetic status, surgeon grade, and operative complications were included as variables for analysis. Results: Data were available for 4047 cataract operations. Of these, 108 (2.7%) had undergone previous anti-VEGF IVI treatment. Three eyes were noted to have preoperative PC trauma and were excluded from the final analysis. The logistic regression analysis after exclusion of the eyes with pre-existing damage to the PC confirmed that previous anti-VEGF IVI treatment was associated with an increased risk of PCR when compared with the non-IVI group (6.67% vs 1.88%, P < .0001). There is a dose-dependent relationship between the number of anti-VEGF injections and the likelihood of PCR. Conclusions: Previous intravitreal anti-VEGF injections are significantly correlated with an increased risk of surgical PCR, despite the absence of visible structural damage to the posterior capsule preoperatively.